Geopolymer concrete-filled aluminium alloy tubular cross-sections. (May 2023) - Gkantou, Michaela; Georgantzia, Evangelia; Kadhim, Abdullah; Kamaris, George S.; Sadique, Monower
Abstract: Composite steel–concrete members are adopted in structural applications as a cost-effective and high-speed construction practice. Exploiting the superior corrosion and strength-to-weight properties of structural aluminium, research on composite aluminium-concrete members has been reported. Aiming for an even more sustainable and durable structural member, this paper proposes combining structural aluminium alloys with low carbon geopolymer concrete (GC) to form a structural member with lower environmental footprint. To this end, an experimental programme on geopolymer concrete-filled aluminium alloy tubular (GCFAT) cross-sections is performed. A total of 24 tests on stub columns and 12 tests on beams were carried out. In particular, 4 square hollow sections infilled with one-part geopolymer concrete were tested under uniform compression and under uniaxial bending. The hollow sections were fabricated from 6082-T6 heat-treated aluminium alloy. The same cross-sections were also tested as bare and infilled with ordinary Portland cement (OPC) concrete for comparison purposes. It is shown that the strength of the composite sections is significantly increased compared to the bare ones. In particular, the average strength increase was in the range of 16.5%–93.3% and of 23%–93.1% for GC and OPC-aluminium stub columns, respectively. In beams, the strength increase was in the range of 14.1%–53.6% for GC-aluminium and of 10.2%–48.9% for OPC-aluminium specimens. In absence of codified design rules for geopolymer concrete-aluminium structures, design formulae based on the European standards for composite steel–concrete members, with the material properties of steel and concrete replaced by those of aluminium alloy and GC, respectively, are adopted. The obtained results demonstrated that the proposed design methodology is suitable for the design of GCFAT cross-sections and beams, providing reasonably accurate and consistent strength predictions. Overall, the potential of geopolymer concrete-filled aluminium tubular cross-sections as a novel cement-free, sustainable, and structurally efficient composite cross-section is demonstrated.